Relationship between ground reaction forces during walking and physical activity in postmenopause women - João Fonseca (2013)
The menopause triggers an increase in fat mass and visceral fat mass anda reduction in muscle mass of the lower limbs, limiting mobility and functionalautonomy of women (Stergiou et al. 2002). The ground reaction forces (GRF)show the magnitude and duration of the charge applied when the foot is in contactwith the ground (Saad et al. 2011). The study of this association be-comes relevantto prevent musculoskeletal injury and promoting a healthy lifestyle in this type ofwoman.The objective of this study has been the analysis of GRF components vertical andantero-posterior during walking in postmenopausal women, according to the levelsof physical activity. The sample studied included 53 postmenopausal women agedbetween 48 and 69 year. The GRF data was collected using a force platformKistler 9281B, and adopting the 3 steps protocol (Bus et al. 2005).The physical activity was measured using an Actigraph GT1M accelerometer andthe assessment was done in 4 days, including 2 weekend days. The association ofvariables was studied using the R Pearson correlation coefficient, and step-wiseregression models were developed. A statistical level of significance equal to 5%was adopted.The time of moderate-vigorous physical activity (TMVPA) revealed one predictor(p 0.05) independent of the minimum force peak during the support phase (Fz2)(ß= -0.29). The braking peak (ß = -0.32) and the impulse until Fy1 (ß = -0.36) explains8.7% and 10.9% of variation of the latter (EPE=0.02 N.s/kg). The maximumvertical peak during the loading phase of walking cycle (Fz1) (ß=0.34) is influencedin 11,1% by the ageing. The time of menopause (TM) has influence theFz1 loading rate (ß=0.28) and the rating Fz2/Fz1 (ß=-0.31).The results suggest that the TMVPA, age and TM, influence the behavior ofground support, causing differences in the accommodation of the external load 2during the walking cycle, and therefore should be considered in the prevention ofmusculoskeletal disorder